Towards sustainable implementation of maritime spatial planning in Europe: A peek into the potential of the Regional Sea Conventions playing a stronger role. (September 2018) - de Grunt, L.S.; Ng, K.; Calado, H.
Abstract: Traditional silo approaches to managing marine resources and anthropogenic activities are progressively being replaced by systemic and holistic ecosystem-based management. In Europe, authorities are increasingly realising the interconnected complexity and transboundary effects of maritime economic activities on each other and on the marine environment. Facilitating cross-border coordination and cooperation between neighbouring European Member States and their non-EU border countries on the implementation of maritime spatial planning (MSP) is essential in ensuring the sustainable management of the European marine environment. During the last decade, progressive efforts have been dedicated to coordinate national marine planning to ensure that there is a concerted, coherent and sustainable approach regarding the activities taking place in the European seas. The Maritime Spatial Planning Directive (2014/89/EU) states that regional coordination and cooperation between Member States is a requirement in the development and implementation of national maritime spatial plans, and specifically mentions the consideration of the Regional Sea Conventions (RSCs) that are in place in Europe. Through analysing the results of a small-scale survey under European MSP experts, the paper explores whether an increased involvement of the RSCs in regional cooperation on MSP is perceived as possible and/or desirable. The paper considers the (potential) role of the RSCs in the cross-border coordination of major maritime economic activities, as well as in cross-border MSP projects taking place in the European sea basins. The paper pays specific attention to the desirability and perceived challenges of such an increased role for the RSCs. Highlights: Transboundary complexity of marine environment calls for ecosystem-based management. Need for cross-border approach to sustainable, coordinated and coherent MSP. Increased involvement of RSCs in European MSP might be possible/desirable. Limited environmental mandate is a barrier to increased RSCs' involvement in MSP.